Current research progress on the use of traditional Chinese medicine in the treatment of diabetic foot ulcers - Xia, Yinfeng; Wu, Ping; Chen, Yongsong; Chen, Zhiyong (Frontiers in Endocrinology, 2025)
Diabetic foot ulcers represent a significant complication of diabetes mellitus, presenting substantial challenges due to their intricate pathogenesis, which encompasses neuropathy, vasculopathy, chronic inflammation, and biofilm-associated infections. Despite considerable advancements in Western medical interventions, including surgical debridement, skin grafting, negative pressure wound therapy, and innovative dressings, these ulcers remain a leading cause of amputation and contribute to a substantial socioeconomic burden. Traditional Chinese medicine (TCM) has emerged as a promising adjunctive therapy, offering multi-targeted mechanisms that address oxidative stress, chronic inflammation, angiogenesis, and microbial resistance associated with diabetic foot ulcers. This review aims to examine contemporary studies on the application of TCM in the treatment of diabetic foot ulcers, evaluating its efficacy and elucidating its mechanisms of action, thereby providing a reference for clinical treatment decisions and guiding future research directions.